Organic anion recognition of naphthalenesulfonates by steroid-modified β-cyclodextrins : enhanced molecular binding ability and molecular selectivity - Zhao, Yanli (2011)
Two β-cyclodextrin (β-CD) derivatives bearing steroid groups (1 and 2) were synthesized by the condensation of mono(6-aminoethylamino-6-deoxy)-β-CD with cholic acid and deoxycholic acid, respectively, and their original conformations and binding behavior to the organic anion of naphthalenesulfonate derivatives were investigated by using 1H NMR spectroscopy and spectrofluorometric titration in combination with computational methods. The 2D NMR experiments reveal that the steroid groups attached to the β-CD rim could be deeply embedded in the β-CD cavity to form the intramolecular (for 1) or intermolecular (for 2) inclusion complexes in aqueous solution. Upon complexation with naphthalenesulfonate derivatives, modified β-CDs display two obviously different binding modes, that is, the competitive inclusion mode and the induced-fit inclusion mode, which is consistent with the results of molecular modeling study. The two modes and the strict size/shape fitting relationship between the hosts and guests reasonably explain the different binding behaviors and molecular selectivity of host β-CDs 1 and 2 toward the naphthalenesulfonate guests. Therefore, the cholic acid- or deoxycholic acid-modified β-CDs could effectively recognize the size/shape of guest molecules as compared with the parent β-CD, giving good molecular selectivity up to 24.9 for the disodium 2,6-naphthalenedisulfonate/disodium 1,5-naphthalenedisulfonate pair by the host 1.